Partecipazione in Toscana : Interpretazioni e racconti - Camilla Perrone; Anna Lisa Pecoriello; Francesca Rispoli; Giancarlo Paba (Firenze University Press, 2009)
The stories and interpretations of participation that make up this book are the result of research carried out during the drafting of the new law on participation, subsequently approved by the Tuscan Regional Authority (L.R. 69/07). The context is presented in two introductory essays that discuss some of the most relevant issues of participation This is followed by a section consisting of thirty-eight factsheets that critically address several of the Tuscan participatory experiences, broken down into five interpretational 'boxes': governance, decisional democracy, participatory planning, social self-organisation and conflict. Emerging from the cases analysed is a variegated landscape of experiences of interactive planning, with lights and shadows, significant results and difficulties, related primarily to the implementation phase of the projects. The authors seek to recount and valorise certain of the more original and innovative pioneering experiences, and to offer food for thought for the greater spread and enhanced efficacy of participatory practices, interactive planning and social self-organisation.
Keywords: Toscana; Urbanistica; progettazione partecipata